2022
DOI: 10.3390/ijerph192215268
|View full text |Cite
|
Sign up to set email alerts
|

Research on Multi-Scale Ecological Network Connectivity—Taking the Guangdong–Hong Kong–Macao Greater Bay Area as a Case Study

Abstract: The Guangdong–Hong Kong–Macao Greater Bay Area urban agglomeration is an urban agglomeration with some of the most intensive urbanization since 1980s. A large amount of cultivated land, forest land, water bodies and other land types in the region has been occupied by construction land, resulting in fragmented ecological landscapes and biodiversity in the region and causing many other ecological problems. Based on this, this paper takes the Guangdong–Hong Kong–Macao Greater Bay Area as a case study, constructs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…In addition to patch abundance and spatial arrangement, these indices combine the dispersal specificity of plant habitats. Wu et al [ 26 ] took the Guangdong-Hong Kong-Macao Greater Bay Area as an example, and found that the overall ecological connectivity of ecological networks at all scales showed a gradual upward trend, and the overall connectivity index (IIC) and the possible connectivity index (PC) gradually increased with the increase in the maximum dispersal distance of species. Javier Babi Almenar [ 27 ] integrated a landscape index analysis, including the overall connectivity index (IIC), probable connectivity index (PC), and equivalent connectivity index (EC) to show that from 1999 to 2007, habitat fragmentation and loss increased ecological connectivity in Luxembourg, Western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to patch abundance and spatial arrangement, these indices combine the dispersal specificity of plant habitats. Wu et al [ 26 ] took the Guangdong-Hong Kong-Macao Greater Bay Area as an example, and found that the overall ecological connectivity of ecological networks at all scales showed a gradual upward trend, and the overall connectivity index (IIC) and the possible connectivity index (PC) gradually increased with the increase in the maximum dispersal distance of species. Javier Babi Almenar [ 27 ] integrated a landscape index analysis, including the overall connectivity index (IIC), probable connectivity index (PC), and equivalent connectivity index (EC) to show that from 1999 to 2007, habitat fragmentation and loss increased ecological connectivity in Luxembourg, Western Europe.…”
Section: Introductionmentioning
confidence: 99%
“…However, these traditional indicators could not completely set apart multiple morphological layouts with diverse environmental effects [43,44]. In particular, the connecting passageways that will enable the efficient movement of species between various habitats (i.e., ecological corridors) play a prominent part in the conservation of biodiversity [45][46][47][48]. Unfortunately, these narrow-shaped components are very difficult to be automatically generated through spatial optimization techniques [38,49].…”
Section: Introductionmentioning
confidence: 99%